Inhibition of secretin stimulated pancreatic secretion by pancreatic polypeptide. Issue 1 (January 1979) - Adrian, T E; Besterman, H S; Mallinson, C N; Greenberg, G R; Bloom, S R
Abstract : The effect of PP on secretin-stimulated pancreatic secretion was assessed in five healthy subjects. During an intravenous infusion of BPP at a dose which produced plasma levels similar to those seen after meals in healthy young adults the volume and bicarbonate content of duodenal juice was reduced by 25% (p less than 0.05) and 24% (p less than 0.05) respectively, while protein and bilirubin concentrations were more markedly reduced by 68% (p less than 0.0005) and 67% (p less than 0.0005) respectively. PP, thus, may be an important inhibitory factor in the control of bilirubin and pancreatic enzyme secretion in man.